Farm Live-In Program - James L. Bramblett (Journal of Applied Communications, 1974)
The Farm Live-In Program, co-sponsored by the University of Georgia Extension Service and the USDA Office of Communications, was conducted from October 16 to June 30 of last year, reaching an estimated 867,450 readers at a cost of 1.2 cents per reader. (Production note: page 11 wasn't scanned properly.)